Edukasi dan Implementasi Senam Kegel untuk Mencegah Prolapsus Uteri pada Masa Klimakterium dan Menopaus - Endah Saraswati; Sitti Aisa; Sultina Sarita (PT Karya Inovasi Berkelanjutan, 2025)
The climacteric and menopausal periods represent transitional phases in women characterized by a decline in estrogen levels, which increases the risk of uterine prolapse due to weakening of the pelvic floor muscles. One preventive effort that can be undertaken is Kegel exercise. This community service activity aimed to improve the knowledge and skills of women during the climacteric and menopausal periods in performing Kegel exercises as an effort to prevent uterine prolapse. The activity was conducted in September 2022 in Batugong Village, Lalonggasumeeto District, Konawe Regency, involving 40 female participants. The implementation method consisted of a preparation stage, education and implementation of Kegel exercises, and evaluation. Knowledge was measured using pre-test and post-test, while participants’ skills were evaluated after the educational intervention. The results showed an improvement in participants’ knowledge from poor to good among all participants after the education. In addition, the majority of participants demonstrated good ability in performing Kegel exercises. These findings indicate that education and implementation of Kegel exercises are effective in improving women’s knowledge and skills and have the potential to serve as a promotive and preventive intervention to prevent uterine prolapse during the climacteric and menopausal periods.